Plant food anthocyanins inhibit platelet granule secretion in hypercholesterolaemia: Involving the signalling pathway of PI3K–Akt - Song, Fenglin; Zhu, Yanna; Shi, Zhenyin; Tian, Jinju; Deng, Xiujuan; Ren, Jing; Andrews, Marc C.; Ni, Heyu; Ling, Wenhua; Yang, Yan (Thrombosis and Haemostasis, 2014)
Controlling platelet granule secretion has been considered an effective strategy to dampen thrombosis and prevent atherosclerosis. Anthocyanins are natural plant pigments and possess a wide range of biological activities, including cardiovascular protective activity. In the present study we explored the effects and the potential mechanisms of anthocyanins on platelet granule secretion in hypercholesterolemia. In a randomised, double-blind clinical trial, 150 hypercholesterolaemic individuals were treated with purified anthocyanins (320 mg/day) or placebo for 24 weeks. Anthocyanins consumption significantly reduced plasma levels of β-thromboglobulin (β-TG), soluble P-selectin, and of Regulated on Activation Normal T cell Expressed and Secreted (RANTES) as compared with the placebo. A minor reduction in platelet factor 4 (PF4) and transforming growth factor β1 (TGF-β1) levels were also observed. In in vitro experiments, we observed that purified anthocyanin mixture, as well as its two main anthocyanin components, delphinidin-3-glucoside (Dp-3-g) and cyanidin-3-glucoside (Cy-3g) directly inhibited platelet á-granule, dense granule, and lysosome secretion evaluated by P-selectin, RANTES, β-TG, PF4, TGF-β1, serotonin, ATP, and CD63 release. Further, anthocyanins inhibited platelet PI3K/Akt activation and consequently attenuated eNOS phosphorylation and cGMP production, thus interrupting MAPK activation. LY294002, a PI3K inhibitor, did not cause additional inhibitory efficacy, indicating that anthocyanin-induced effects may be involved in inhibition of the PI3K/Akt signalling pathway. These results provide evidence that by inhibiting platelet granule secretion, anthocyanins may be a potent cardioprotective agent.
Keywords: Hypercholesterolaemia; platelet granule; anthocyanins; PI3K